MELAS Missed for Years: Stroke-Like Lesions Are No Indication for Brain Biopsy - J. Finsterer (Case Reports in Neurological Medicine)
A 56-year-old female with a history of chronic alcoholism until age 38 y with a relapse between ages 45 and 46 y developed seizures, psychosis, and hemianopia to the left at age 46 y. Imaging revealed a right parieto-occipital lesion with intralesional bleeding. Five months after the first lesion she developed a second left parieto-occipital lesion, resulting in cortical blindness. Extensive workup, including brain biopsy, was noninformative. Retrospectively, the occipital abnormalities were identified as stroke-like lesions (SLLs). Further manifestations of the mitochondrial disorder (MID) were tremor, cerebral atrophy, bilateral basal ganglia, calcification, glaucoma, hypoacusis, short stature, hyperostosis frontalis, hyperthyroidism, sick-sinus syndrome and AV-block-1, and myopathy. According to the Walker criteria, a possible MID was diagnosed. In conclusion, adult-onset MID may be missed for years, SLLs may be easily misinterpreted entailing brain biopsy, and psychosis may contribute to a reduced impact for proper workup of a MID.